2011
DOI: 10.1002/app.34217
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial nanocellulose‐reinforced arabinoxylan films

Abstract: There is an increasing interest in substituting today's films for food packaging applications with films based on renewable resources. For this purpose, rye arabinoxylans, unmodified and enzymatically debranched, were studied for the preparation of neat films and composite films reinforced with bacterial cellulose (BC). Mixing in a homogenizer produced optically transparent, uniform films. Physical and mechanical characteristics of such films are here reported. Debranching of the arabinoxylan caused an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 42 publications
5
29
2
Order By: Relevance
“…4b. MFC absorbed large amount of water in comparison to bacterial cellulose studied previously (Stevanic et al 2011). This could be due to the hydrophilic carboxymethyl groups present in MFC.…”
Section: Water Sorptionmentioning
confidence: 97%
See 1 more Smart Citation
“…4b. MFC absorbed large amount of water in comparison to bacterial cellulose studied previously (Stevanic et al 2011). This could be due to the hydrophilic carboxymethyl groups present in MFC.…”
Section: Water Sorptionmentioning
confidence: 97%
“…The quality of fibrillation had an impact on the reinforcement potential of MFC (Zimmermann et al 2010). In our previous study, stronger and stiffer rye arabinoxylan-based films were produced by adding bacterial cellulose (Stevanic et al 2011). The aim of the present study was to prepare wood-based composite films by using MFC as a reinforcement of GGM.…”
mentioning
confidence: 99%
“…In addition to the barrier properties and related functional capabilities of nanocellulose-based layers, much research has focused on desirable attributes such as transparency Petersson and Oksman 2006;Nordqvist et al 2007;Shimazaki et al 2007;Ayuk et al 2009;Fernandes et al 2009Fernandes et al , 2010Fukuzumi et al 2009;Kim et al 2009;Nogi et al 2009;Petersson et al 2009;Sehaqui et al 2010;Hassan et al 2011;Pereda et al 2011Pereda et al , 2014Stevanic et al 2011;Yang et al 2011;Aulin et al 2012;Hu et al 2013;Li et al 2013a;Tome et al 2013;Khan et al 2014b;Kumar et al 2014;Kurihara and Isogai 2014;Tammelin and Vartiainen 2014;Ambrosio-Martin et al 2015b;Honorato et al 2015;Oun and Rhim 2015;Toivonen et al 2015a,b). Hu et al (2013) showed that nanocellulose films could be rendered conductive by deposition of tindoped indium oxide, while still retaining their transparency; solar cells prepared with such films were successfully demonstrated.…”
Section: Transparencymentioning
confidence: 99%
“…In recent years, various polymeric applications manufactured from LCMs have gained growing attention (Edlund et al 2011;Stevanic et al 2011;Wang et al 2012;Oinonen et al 2013). In this approach, hemicelluloses represent many promising properties for the manufacture of value-added polymeric composites and blends, which could replace materials currently manufactured from fossil resources or even metals, such as aluminum (Alekhina et al 2014).…”
Section: Polysaccharide-based Biodegradable Films and Hydrogelsmentioning
confidence: 99%
“…These bio-based polymers can be used instead of aluminum foil or synthetic polymers, resulting in the decreased carbon footprint of the packaging industry Alekhina et al 2014). Hemicelluloses-derived polymers are hydrophilic, and as such, they demonstrate notable barrier characteristics against oils and fats (Stevanic et al 2011). However, water vapor permeability and oxygen permeability also are crucial properties, especially when considering many food packaging applications (Mikkonen et al 2010).…”
Section: Polysaccharide-based Biodegradable Films and Hydrogelsmentioning
confidence: 99%